(untitled) (Journal of Environmental Bioremediation and Toxicology, 2024)
This research presents the characterization of Pseudomonas sp. strain Neni-4 , which was selected because it can metabolize phenol as its primary carbon source. The strain breaks down phenol through the meta-cleavage pathway , which is typical for many efficient phenol-degrading bacteria. The strain achieved its highest growth rate at temperatures ranging from 25 to 30°C and pH values between 7.0 and 7.5 without significant differences (p > 0.05) in these ranges. The bacterial growth reached its peak when phenol concentrations ranged from 500 to 700 mg/L. The best growth results occurred when using 1% (w/v) ammonium sulfate as the nitrogen source. The research investigated the impact of heavy metals on the phenol breakdown process. Cd(II) showed no inhibitory effect on the process , and similarly, Pb(II) and Ni(II) showed more than 90% activity was observed. The growth rate decreased by 27% when exposed to Cu(II), but Ag(I) and Hg(II) caused extreme inhibition, which reduced activity to 12% and 5% respectively. The degradation profile indicated a rapid decrease of phenol concentration from 500 mg/L to near-zero levels during the first five days, while the cell density increased, indicating active biodegradation. Pseudomonas sp. strain Neni-4 demonstrates potential for bioremediation of phenol-contaminated sites when operated under neutral pH and mesophilic temperature conditions.